PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MODEL PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN PERMAINAN LINGKARAN BACA PADA SISWA KELAS I UPT SDN 11 MAKALE - Apriani; Salu Situru, Roberto; Salu, Benyamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to enhance the early reading skills of first-grade students at UPT SDN 11 Makale through the application of cooperative learning models combined with the reading circle game approach. Early reading skills are fundamental to academic success, yet many students face challenges in mastering these skills, which impacts their overall learning motivation. This research employs a Classroom Action Research (CAR) method, involving two cycles of planning, action, observation, and reflection. Data were collected through observations, tests, and interviews with both students and teachers. The results show a significant improvement in students' reading skills from the first cycle to the second cycle. The average score of students increased from 73.95% in the first cycle to 83.3% in the second cycle, with the completion rate rising from 74.10% to 90.27%. The implementation of the cooperative learning model with the reading circle approach not only improved reading fluency but also enhanced student engagement and motivation. This research demonstrates the effectiveness of interactive and collaborative learning methods in improving early reading abilities in young learners